Angiocentric glioma-associated seizures: The possible role of EATT2, pyruvate carboxylase and glutamine synthetase. (March 2021) - Buccoliero, Anna Maria; Caporalini, Chiara; Scagnet, Mirko; Mussa, Federico; Giordano, Flavio; Sardi, Iacopo; Migliastro, Irene; Moscardi, Selene; Conti, Valerio; Barba, Carmen; Antonelli, Manila; Gianno, Francesca; et al.
Highlights: Patients affected by angiocentric glioma frequently experience drug resistant seizures. Elevated concentrations of glutamate may determine neuronal hyperexcitability. Altered expression of EAAT2, pyruvate carboxylase and glutamine synthetase causes elevated concentrations of glutamate. Angiocentric gliomas loose EAAT2 expression. Abstract: Purpose: Our purpose was to better understand the pathogenesis of seizures associated with angiocentric glioma. Angiocentric glioma is an indolent and rare low-grade glioma. Its typical clinical presentation is with epileptic seizures. The pathogenesis of tumor-associated seizures is poorly understood. Among the possible pathomechanisms, the increased neurotoxic concentrations of the glutamate has been proposed. Glutamate transporters, pyruvate carboxylase and glutamine synthetase are involved in maintaining the physiological concentration of glutamate in the inter synaptic spaces. Methods: We evaluated the immunohistochemical expression of EAAT2 (the most important glutamate transporter), pyruvate carboxylase and glutamine synthetase in 17 angiocentric gliomas. Results: EAAT2 was never expressed (0%) in the neoplastic cells in none of the cases studied. Pyruvate carboxylase was expressed in the cytoplasm of the neoplastic cells in 16/17 cases (94 %). Glutamine synthetase was expressed in the cytoplasm of the neoplastic cells in 15/17 cases (88 %). Conclusion: The net result of this enzymatic expression, in particular considering the loss of EAAT2, could be an increased glutamate concentration in the synaptic clef, which might increase local network excitability initially involving intratumoral neurons. The observation that the angiocentric glioma-associated epilepsy might be at least in part related to EAAT2 deficiency opens up interesting therapeutic perspectives.